Przyjaciel czy wróg? Ambiwalencja wody na przykładzie wybranych opisów niderlandzkiego budownictwa hydrotechnicznego - Sebastian Latocha (Studia Etnologiczne i Antropologiczne, 2018)
Flood is not an episode in the history of the Netherlands, but a recurring fact of nature and social experience. The Dutch struggle against water (this metaphor seems to dominate the descriptions of the Netherlands) is not only troublesome and strenuous, but its significance also happens to be assessed in a positive way. In the literature indicated by the author, fascination with the capriciousness of the element of water and Dutch water engineering (satisfying a tourist‘s appetite?) takes prece‑ dence over the catastrophic and empathic discourse of lamentation. The article is an interpretation of the Dutch model of struggling against the element of water through the prism of anthropological categories of culture and nature. The exemplifications come from travel literature, tourist guides and scientific monographs, the reading of which shows that the mutual relationship (symbiosis) of the water element and cul‑ ture, the mentality of the Dutch who struggle with nature is the reoccurring concept scheme. What is the main feature of the aquatic element is the ambivalent influence of water on Dutch culture. It is Dutch fairy tales that may prefigure this ambivalence.